The production of spaces of the 'good life' – the case of lifestyle migrants in Spain. Issue 2 (3rd March 2016) - Kordel, Stefan
Abstract : In search for the 'good life', the current generation of European retirees is striving to materialise a self-determined way of life by moving to locations that provide a higher quality of life, such as the Mediterranean coast. Migrants' leisure practises and distinct spatial features, e.g. leisure infrastructures, hereby frame a production of desirable spaces. The contribution is theoretically informed by Henri Lefebvre's theory of the production of space that suggests space to be a social product emerging from congruities and contradictions in a triad of practices, representations and localities. It is discussed how everyday leisure practices reproduce collectively or individually imagined representations of spaces of the 'good life' and how such spaces are contested. The presented case study is mainly based on qualitative interviews depicting narratives associated with the realm of leisure. Empirical data were collected among German retirees, who relocated to a small municipality at the Costa del Sol (Southern Spain). The analysis of empirical data reveals mostly consistencies within the realms representations, practices and localities, but depicts contestations of spaces of the 'good life' with regard to ongoing ageing processes. Lifestyle migrants ascribe meaning to practices of leisure in order to fulfil the desire for consuming tourist; sights that frequently represent highly symbolic places. Constructing notions of sociability with friends and acquaintances through leisure, the migrants hold meaningful social ties, which provide security through reliable networks. Nevertheless, this article points out that spaces of the 'good life' are deconstructed through age-related mobility constraints.